Immunohistochemistry of Janus Kinase 1 (JAK1) Expression in Vitiligo - Asmaa Gaber Abdou; Alaa Maraee; Hossam Yassien; Mona Sarhan (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Background Vitiligo is a chronic autoimmune disease in which the destruction of melanocytes causes white spots on the affected skin. Janus kinase (JAK) is a family of intracellular, non-receptor tyrosine kinases that transduce cytokine-mediated signals via the JAK-signal transducer and activator of transcription pathway. The aim of the present study is to explore the possible role of JAK1 in the pathogenesis of vitiligo using immunohistochemical methods. Methods The current study was conducted in a sample of 39 patients who presented with vitiligo and 22 healthy individuals who were age and sex matched as a control group. We used immunohistochemistry to evaluate JAK1 status (intensity and distribution) and assess the percentage of residual melanocytes using human melanoma black 45 (HMB45). Results Intense and diffuse JAK1 expression was significantly more likely to indicate vitiliginous skin compared to normal skin (p < .001). Strong and diffuse JAK1 expression was associated with short disease duration, female sex, and lower percentage of melanocytes (detected by HMB45) (p < .05). Conclusions JAK1 may be involved in the pathogenesis of vitiligo, as indicated by intense and diffuse expression compared to control and association with lower percentage of melanocytes detected by HMB45 immunostaining.